2015
DOI: 10.12816/0011360
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Association of Signs and Symptoms of Temporomandibular Disorders with Missing Posterior Teeth in Adult Jordanian Subjects

Abstract: Objectives: To determine the prevalence of temporomandibular disorders (TMD) in adult Jordanian subjects with missing posterior teeth and the association of signs and symptoms of TMD with missing posterior teeth. Methods: A questionnaire and clinical examination were used to assess 93 subjects who accepted to participate in this study and were selected according to specific inclusion criteria. They were asked about TMD-related symptoms (pain or tenderness in the jaw joint and/or muscles of mastication, joint s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
2
4
0
2
Order By: Relevance
“…9 In this study no relationship between clicking and missing teeth were found and this claimed that logistic regression analysis explained that missing teeth was majorly connected with TMDs and clinical sign of joint sound. 10 The results of this study coincide with the hypothesis that the exact etiology of TMDs is still obscure, and there is a lack of a clear single cause of TMDs, specially clicking, and a multifactorial etiology has been thus proposed.…”
Section: Discussionsupporting
confidence: 85%
“…9 In this study no relationship between clicking and missing teeth were found and this claimed that logistic regression analysis explained that missing teeth was majorly connected with TMDs and clinical sign of joint sound. 10 The results of this study coincide with the hypothesis that the exact etiology of TMDs is still obscure, and there is a lack of a clear single cause of TMDs, specially clicking, and a multifactorial etiology has been thus proposed.…”
Section: Discussionsupporting
confidence: 85%
“…Osteoarthrosis is one of the degenerative joint diseases on the articular surface that is often found in the elderly. 17 Manchikalapudi et al 28 in his study stated that the loss of support in posterior teeth is also considered to significantly increase the risk of osteoarthrosis. Osteoarthrosis has an uneven articular surface appearance due to fibration, erosion, and cracks in the superficial layer of cartilage in the TMJ.…”
Section: Figurementioning
confidence: 99%
“…Adjustment of new functional chewing can cause changes in the trajectory of the TMJ movement. 17 In normal joint movement, the disc is located directly on the head of the condyle. The articular disc will be between the mandibular condyle and the posterior slope of the articular eminence in the normal functional state when the jaw closes.…”
Section: Figurementioning
confidence: 99%
“…Gangguan temporomandibula (TMD) adalah istilah umum untuk berbagai tanda dan gejala klinis yang melibatkan otot pengunyahan, sendi temporomandibular (TMJ) dan struktur orofasial yang terkait. 1 Gangguan temporomandibula memiliki gejala klinis yang dapat berupa rasa nyeri pada sendi wajah, nyeri pada sendi rahang, bunyi pada sendi mandibula, kesulitan dalam menutup dan membuka mulut, rasa tidak nyaman ataupun rasa nyeri ketika menggigit atau mengunyah makanan, serta gerak rahang yang terbatas. 2 TMD dengan rasa nyeri dapat mengganggu aktivitas sehari-hari, fungsi psikososial, dan kualitas hidup.…”
Section: Pendahuluanunclassified